Workflow and Human-Centered Risk Analysis for Novel Mechatronic Rescue Aids I. - Drobinsky Sergey (De Gruyter, 2020)
Paramedics face rising numbers of deployments every year. As obstacles like stairs occur often, paramedics must frequently manually carry patients and are thereby exposed to loads multitudes higher than recommended. This creates the need for patient transport aids (PTA), which can physically support paramedics in a wide variety of transport situations, without slowing down the transport. In this paper a workflow analysis for transport missions in an urban context and basic tasks for PTAs are presented. Subsequently, the high-level task modelling and human-centered risk analysis according to the HiFEM method are presented for the use case of a patient transport over stairs with a passive PTA, like a rescue chair, and an active PTA like the novel SEBARES prototype. The analysis shows that conventional PTA’s have a simple linear use process, however, impose excessive physical workloads, which cause risks like the paramedic or the PTA falling down the stairs. Contrary, active PTA’s reduce physical workloads, however, introduce additional concurrent steps, like identifying and correcting misalignments, which create further risks. In order to mitigate risks with active, stair climbing PTAs either new kinematic designs or intelligent assistance functions, like automatic stair detection, are necessary.